2019
DOI: 10.3389/fimmu.2019.01331
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Circulating Naïve CD4+ and CD8+ T Cells Recognizing Nickel

Abstract: Allergic contact dermatitis caused by contact sensitizers is a T-cell-mediated inflammatory skin disease. The most prevalent contact allergens is nickel. Whereas, memory T cells from nickel-allergic patients are well-characterized, little is known concerning nickel-specific naïve T-cell repertoire. The purpose of this study was to identify and quantify naïve CD4+ and CD8+ T cells recognizing nickel in the general population. Using a T-cell priming in vitro assay based on autologous co-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 54 publications
(80 reference statements)
3
21
0
Order By: Relevance
“…This technique is being increasingly used to identify pathogenic T cells in many different immune-mediated diseases [ 28 , 29 ]. In this study, we showed several highly expanded T cell clones by sequencing data, and demonstrated the preferential usage of TRBV19, TRBV5-1, and TRBV20-1, consistent with previous studies on Ni 2+ contact dermatitis [ 11 , 16 , 18 , 20 ]. Our study suggests, then, that the certain population of Ni 2+ -reactive T cells in joint implant failure may be shared with the T cells responsible for Ni 2+ induced contact dermatitis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This technique is being increasingly used to identify pathogenic T cells in many different immune-mediated diseases [ 28 , 29 ]. In this study, we showed several highly expanded T cell clones by sequencing data, and demonstrated the preferential usage of TRBV19, TRBV5-1, and TRBV20-1, consistent with previous studies on Ni 2+ contact dermatitis [ 11 , 16 , 18 , 20 ]. Our study suggests, then, that the certain population of Ni 2+ -reactive T cells in joint implant failure may be shared with the T cells responsible for Ni 2+ induced contact dermatitis.…”
Section: Discussionsupporting
confidence: 91%
“…The ternary structure of the ANi2.3 TCR, MHC and mimotope confirmed that Ni 2+ presentation required both a specific MHC and peptides [ 15 ]. Recently, a study by Bechara et al also showed the dominant usage of TRBV19 in highly expanded clones from Ni 2+ -specific naive T cell lines derived from Ni 2+ sensitized contact dermatitis subjects [ 16 ]. However, another paper found dominant usage of TRAV9-2 rather than TRBV19 in CD154 positive nickel-stimulated T cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, activated NK cell might amplify the immune reaction via secretion of IFN‐γ, additionally activating dendritic cells, which leads to enhanced T‐cell responses. Furthermore, nickel‐specific CD4+ and CD8+ T cells have been described in nickel‐allergic patients being capable to produce IFN‐γ and granzyme B 40 . Earlier studies suggest that CD8+ T cells selectively kill human IFN‐γ‐primed keratinocytes, rendering them prone toward T H 1‐dependent cytotoxicity 41 .…”
Section: Discussionmentioning
confidence: 99%
“…So far, a comprehensive analysis of the Ni‐reactive TCR repertoire has been missing due to technological limitations. Only β‐chains were analyzed because many V segment antibodies are available and the limited number of J segments facilitates multiplex PCR approaches 22,25,26 …”
Section: Introductionmentioning
confidence: 99%